Giant intradiverticular bladder tumor with narrow diverticular neck (Indian Journal of Case Reports, 2025)
Intradiverticular bladder tumors (IDBT) are rare entities that constitute 1% of all malignancies of the urinary bladder. They present diagnostic and therapeutic challenges. Imaging is crucial in diagnosing this condition. Here we reported a case of a 65-year-old male who presented to our center with severe lower urinary tract symptoms for 9 months, accompanied by weight loss, nausea, vomiting, and an absence of visible hematuria. Clinical examination revealed a palpable suprapubic mass. Laboratory investigations showed low hemoglobin levels, microscopic hematuria, and raised renal function tests. Computed tomography showed a giant bladder diverticulum housing a solid tissue mass. Cystoscopy was challenging due to a narrow diverticular neck. A midline incision was made, and diverticulectomy was performed; histopathological examination revealed high-grade urothelial carcinoma with concurrent right iliac lymph node metastasis. This case highlights the diagnostic challenges of IDBT and emphasizes the importance of a thorough investigation of bladder diverticula to avoid missing intradiverticular malignancy.